2021
DOI: 10.1016/j.nicl.2021.102794
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between white matter microstructure and self-perceived cognitive decline

Abstract: Highlights RD T within several white matter tracts is associated with SCD. RD T contributes unique variance to SCD beyond that of CSF Aβ 42 . Our findings suggest that RD T is a sensitive marker of SCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 70 publications
2
7
0
Order By: Relevance
“…Although the relationship between baseline hippocampal volume and fornix FA with long-term memory change were in the expected direction, baseline hippocampal free-water was the only metric that reached significance in MA+ ASD. Our findings agree with our previous work and others who have shown free-water is more sensitive for detecting neurodegeneration in mild cognitive impairment, Alzheimer's, and Parkinson's disease than traditional MRI metrics, such as hippocampal volume and FA (Ofori et al, 2015a(Ofori et al, , 2017(Ofori et al, , 2019Guttuso et al, 2018;Reas et al, 2018;Archer et al, 2021;Dzieciol et al, 2021;Shahid et al, 2022;Zhou et al, 2022). We have previously shown baseline free-water in the substantia nigra predicts cognitive decline associated with Parkinson's disease (Ofori et al, 2015b), and others have demonstrated that baseline hippocampal free-water was a stronger predictor of follow-up cognitive status in Parkinson's disease than hippocampal volume or conventional DTI metrics (Guttuso et al, 2021).…”
Section: Baseline Hippocampal System Correlates Of Memory Declinesupporting
confidence: 93%
See 1 more Smart Citation
“…Although the relationship between baseline hippocampal volume and fornix FA with long-term memory change were in the expected direction, baseline hippocampal free-water was the only metric that reached significance in MA+ ASD. Our findings agree with our previous work and others who have shown free-water is more sensitive for detecting neurodegeneration in mild cognitive impairment, Alzheimer's, and Parkinson's disease than traditional MRI metrics, such as hippocampal volume and FA (Ofori et al, 2015a(Ofori et al, , 2017(Ofori et al, , 2019Guttuso et al, 2018;Reas et al, 2018;Archer et al, 2021;Dzieciol et al, 2021;Shahid et al, 2022;Zhou et al, 2022). We have previously shown baseline free-water in the substantia nigra predicts cognitive decline associated with Parkinson's disease (Ofori et al, 2015b), and others have demonstrated that baseline hippocampal free-water was a stronger predictor of follow-up cognitive status in Parkinson's disease than hippocampal volume or conventional DTI metrics (Guttuso et al, 2021).…”
Section: Baseline Hippocampal System Correlates Of Memory Declinesupporting
confidence: 93%
“…We were the first to establish that this novel, advanced DTI measure which is more sensitive for detecting neurodegeneration in mild cognitive impairment, Alzheimer's disease, and Parkinson's disease than conventional MRI metrics (Ofori et al, 2015a(Ofori et al, , 2017(Ofori et al, , 2019. These findings have since been replicated by other laboratories (Guttuso et al, 2018;Reas et al, 2018;Archer et al, 2021;Dzieciol et al, 2021;Shahid et al, 2022;Zhou et al, 2022). Most recently, Guttuso et al (2021) demonstrated that baseline hippocampal free-water was a stronger predictor of follow-up cognitive status in Parkinson's disease than hippocampal volume or conventional DTI metrics.…”
Section: Introductionmentioning
confidence: 78%
“…30 In this study, WM changes associated with normal brain aging were observed in older healthy adults relative to younger healthy adults, especially in the CG, IFOF, ILF, and UF which have previously been shown to be linked to higher-order cognitive functions. 31,32 These findings show that aging can affect WM microstructural integrity and is, therefore, an important consideration when assessing structural integrity of cerebral WM pathways in the brains of IHD patients undergoing both aging and vascular-related changes.…”
Section: Discussionmentioning
confidence: 81%
“…In conclusion, as no preliminary studies have been performed regarding the associations between cognitive performance and these SNPs in FTD, these results highlight the value of incorporating multiple biomarkers to help disentangle the mechanistic heterogeneity of cognitive decline ( 46 ). Our results may constitute a starting point for future studies involving these SNPs and their relationship with cognitive performance in patients with a probable diagnosis of FTD.…”
Section: Discussionmentioning
confidence: 97%